REKONSTRUKSI HUKUM WAKAF PRODUKTIF DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH DAN PEMBANGUNAN BERKELANJUTAN - Alimuddin, Subkhan; septy, tentiasih (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze and reconstruct the concept of productive waqf within the framework of Islamic economic law by integrating the principles of maqāṣid al-sharī‘ah and sustainable development. Productive waqf has significant potential as an Islamic social finance instrument that functions not only as religious philanthropy but also as a mechanism for economic empowerment, social equity, and environmental sustainability. However, this potential remains underutilized due to regulatory limitations, weak institutional governance, and the low professionalism of nazhir. This research adopts a qualitative approach using a normative juridical method, complemented by conceptual and comparative approaches. Data were collected through library research on statutory regulations, Islamic economic law literature, and relevant previous studies. The findings indicate that the reconstruction of productive waqf law should emphasize a maslahah-oriented impact approach, strengthen nazhir professionalism, and integrate Islamic financial innovation and digital technology. Such reconstruction is essential to ensure that productive waqf plays a sustainable role in supporting economic, social, and environmental development.